2020
DOI: 10.3390/ani10040717
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Antioxidant Enzyme Activity and Related Gene Expression Following Adult Zebrafish (Danio rerio) Exposure to Dimethyl Phthalate

Abstract: Dimethyl phthalate (DMP) is a widespread environmental contaminant that poses potential toxicity risks for animals and humans. However, the toxicological effects of DMP on fish have not been adequately examined. In this study, the acute toxicity, oxidative damage, antioxidant enzyme activities, and relative gene expression patterns were investigated in the liver of adult zebrafish (Danio rerio) exposed to DMP. We found that the lethal concentration (LC50) of DMP for zebrafish after 96 h of exposure was 45.8 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 54 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…The SOD activity in untreated samples showed a declining trend with a significant decrease of ~1.2-fold at 70 ppm ( p < 0.001) which continued to decline by ~1.5-fold at 110 ppm, which may be attributed to a high level of oxidative stress generated beyond the preventive potential of the existing SOD level [ 37 ]. Similar decreasing trends in SOD activities are reported wherein zebrafish larvae were exposed to increasing dimethyl phthalate concentration [ 38 ] or pesticide endosulfan [ 39 ]. In treated samples, SOD activity was found to be relatively closer to the control for initial concentrations and marginal decline at the maximum concentration, i.e., 110 ppm ( p < 0.01).…”
Section: Resultssupporting
confidence: 77%
“…The SOD activity in untreated samples showed a declining trend with a significant decrease of ~1.2-fold at 70 ppm ( p < 0.001) which continued to decline by ~1.5-fold at 110 ppm, which may be attributed to a high level of oxidative stress generated beyond the preventive potential of the existing SOD level [ 37 ]. Similar decreasing trends in SOD activities are reported wherein zebrafish larvae were exposed to increasing dimethyl phthalate concentration [ 38 ] or pesticide endosulfan [ 39 ]. In treated samples, SOD activity was found to be relatively closer to the control for initial concentrations and marginal decline at the maximum concentration, i.e., 110 ppm ( p < 0.01).…”
Section: Resultssupporting
confidence: 77%
“…In the larvae exposed to ( S )‐VEN, there was a decrease in SOD activity at 30 and 3000 μg/L compared to the control (Supporting Information,Table D). This decrease in SOD activity is associated with the decrease in previously observed ROS levels, because the SOD plays an important role in the first defence system (Cong et al, 2020) when ROS levels increased. Catalase activity increased significantly in larvae exposed to 30 μg/L of ( R,S )‐VEN compared to the control but no differences were observed for ( R )‐VEN and ( S )‐VEN.…”
Section: Resultsmentioning
confidence: 81%
“…We observed downregulation of sod1 , sod2 and sod3 by all the doses of DINCH. It has previously been indicated that these genes were affected by several plasticizers such as DEHP, dimethyl phthalate (DMP), and butyl benzyl phthalate (BBP) in zebrafish and medaka fish ( Cong et al., 2020 ; Yang et al., 2018 ; Zhang et al., 2014 ). It has also been shown that SOD1 enzyme activity was overexpressed in response to subacute exposure to DINCH at post-natal day 21 of dams, while it was repressed upon in utero exposure to DINCH at post-natal day 60 in a dose-dependent manner ( Campioli et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%